Assessment of Benthic Ecological Quality Status Using Multi-Biotic Indices Based on Macrofaunal Assemblages in a Semi-Enclosed Bay - Lu, Xin; Xu, Jing; Xu, Zhaodong; Liu, Xiaoshou (Frontiers in Marine Science, 2021)
Semi-enclosed bays have physical and chemical characteristics influenced by both land and sea systems and the quality of the benthic environment is always of great concern. Macrofauna are considered good indicators for evaluating the benthic ecological quality status owing to their biological characteristics. In this study, six biotic indices, namely the Shannon-Wiener diversity index (H'), Abundance-Biomass Comparison (ABC) curve, AZTI's Marine Biotic Index (AMBI), multivariate-AMBI (M-AMBI), BOPA index, and BENTIX index, were used to evaluate the adaptability of different biological indices in the bioassessment of the benthic environment in a semi-enclosed bay. In the annual environmental assessment of the study area, the average values of the six indices (H', ABC curve, AMBI, M-AMBI, BOPA, and BENTIX) were 4.494, 0.182, 2.433, 0.791, 0.033, and 3.813, respectively; accordingly, H', M-AMBI, and BOPA met the high standards whereas the other indices met the good standard, indicating that the whole study bay was slightly disturbed and had good ecological quality. From the perspective of spatial variation, the benthic environment in the middle of the bay was better than that in the north; the environmental problems in the northeast were particularly noteworthy. In terms of temporal patterns, the benthic environment in winter and summer was significantly better than that in spring and autumn, with obvious seasonal differences. The present results indicate that the H' and ABC curve based on benthic abundance and biomass should be avoided for environmental assessment in mariculture areas. AMBI and M-AMBI should be used with caution when the percentage of unassigned species is high, in which case H' is the appropriate choice. When there are few unassigned species, M-AMBI is more conducive for accurate evaluation of the benthic environment than AMBI and H'.